2022
DOI: 10.1017/jfm.2022.116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle geometry on squirming through a shear-thinning fluid

Abstract: Biological and artificial microswimmers often encounter fluid media with non-Newtonian rheological properties. In particular, many biological fluids such as blood and mucus are shear-thinning. Recent studies have demonstrated how shear-thinning rheology can impact substantially the propulsion performance in different manners. In this work, we examine the effect of geometrical shape upon locomotion in a shear-thinning fluid using a prolate spheroidal squirmer model. We use a combination of asymptotic analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 79 publications
3
37
0
Order By: Relevance
“…A similar conclusion is reached for a wide range of spheroidal shape swimmers, and it is found that spheroidal swimmers compared to spherical squirmers can reach higher swimming velocity and energetic efficiency in shear-thinning fluids (van Gogh et al. 2022). In addition, it is shown that the nonlinear rheology of the fluid can modify the efficient swimming gaits in non-Newtonian fluids compared to Newtonian fluids, and allows non-motile surface actuation modes in Newtonian fluids to generate net motion in shear-thinning fluids (Pietrzyk et al.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…A similar conclusion is reached for a wide range of spheroidal shape swimmers, and it is found that spheroidal swimmers compared to spherical squirmers can reach higher swimming velocity and energetic efficiency in shear-thinning fluids (van Gogh et al. 2022). In addition, it is shown that the nonlinear rheology of the fluid can modify the efficient swimming gaits in non-Newtonian fluids compared to Newtonian fluids, and allows non-motile surface actuation modes in Newtonian fluids to generate net motion in shear-thinning fluids (Pietrzyk et al.…”
Section: Introductionsupporting
confidence: 61%
“…2020; van Gogh et al. 2022). When both the swimmer and the inter-fluid boundary are spherical or ellipsoids, these models are analytically tractable and consequently can be used to produce exact results for a wide range of parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By employing the squirmer model, it is shown that while a swimmer slows down in a shear-thinning fluid, they could have higher swimming efficiency and their maximum swimming efficiency occurs at a particular boundary actuation rate [27]. A similar conclusion is reached for a wide range of spheroidal shape swimmers and it is found that spheroidal swimmers compared to over spherical squirmers, can reach higher swimming velocity and energetic efficiency in shear-thinning fluids [17]. In addition, it is shown that the nonlinear rheology of the fluid can modify the efficient swimming gaits in non-Newtonian fluids compared to Newtonian fluids and allows non-motile surface actuation modes in Newtonian fluids to generate net motion in shear-thinning fluids [15].…”
Section: Introductionmentioning
confidence: 57%
“…Similar to many other researches, these studies used an idealized model of a swimmer as a squirmer [8][9][10]. The squirmer model has been employed to study the locomotion in various complex fluids [11][12][13][14][15][16][17]. When both the swimmer and the inter-fluid boundary are spherical or ellipsoids, these models are analytically tractable and consequently can be used to produce exact results for a wide range of parameters.…”
Section: Introductionmentioning
confidence: 99%